Zespół Aspergera = Asperger syndrome - Beck, Oliwia; Łakomski, Mateusz; Radzimińska, Agnieszka; Weber-Rajek, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Beck Oliwia, Łakomski Mateusz, Radzimińska Agnieszka, Weber-Rajek Magdalena, Żukow Walery. Zespół Aspergera = Asperger syndrome. Journal of Education, Health and Sport. 2016;6(7):652-663. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.151590 http://ojs.ukw.edu.pl/index.php/johs/article/view/3866 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Zespół Aspergera Asperger syndrome Oliwia Beck1,2, Mateusz Łakomski1, Agnieszka Radzimińska3, Magdalena Weber-Rajek3, Walery Żukow4 1Katedra i Klinika Geriatrii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, UMK w Toruniu 2Katedra Zdrowia Publicznego, Wydział Nauk o Zdrowiu, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu 3Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, UMK w Toruniu 4Uniwersytet Kazimierza Wielkiego, Bydgoszcz Słowa kluczowe: zespół Aspergera Key words: Asperger syndrome Abstrakt Zespół Aspergera - jedno z pięciu ogólnych zaburzeń rozwoju charakteryzujące się poważnymi trudnościami w kontaktach społecznych i ograniczonym, stereotypowym, powtarzającym się repertuarem zainteresowań i aktywności. Autyzm różni się przede wszystkim tym, że mowa i zdolności poznawcze, są znacznie nie naruszone. Zespół ten jest często określana jako ciężka niezręczność. Zespół Aspergera należy do kategorii całościowych zaburzeń rozwoju. W systemie klasyfikacji – DSM-5 – zespół Aspergera nie występuje, natomiast występuje spektrum zaburzeń autystycznych. Do objawów zespołu Aspergera zalicza się: zaburzenia komunikacji werbalnej i niewerbalnej, egocentryzm, upośledzenie umiejętności społecznych, stereotypowość zachowań, zawężenie zainteresowań, problemy z koordynacją. Manifestacja symptomów zmienia się w ciągu życia. Postawienie właściwej diagnozy jest trudne, szczególnie u osób dorosłych. Najczęściej dzieci z zespołem Aspergera nie wymagają leczenia farmakologicznego. Niekiedy zastosowanie leków może być zalecone ze względu na objawy towarzyszące - depresyjne, lękowe, nasilone rytuały, natręctwa. Leki mogą być również stosowane w przypadku nasilonych zaburzeń koncentracji uwagi, impulsywności i nadmiernej ruchliwości, agresji. Sposób dawkowania zwykle nie wymaga ich podawania na terenie szkoły. Abstract Zespół Aspergera - jedno z pięciu ogólnych zaburzeń rozwoju charakteryzujące się poważnymi trudnościami w kontaktach społecznych i ograniczonym, stereotypowym, powtarzającym się repertuarem zainteresowań i aktywności. Autyzm różni się przede wszystkim tym, że mowa i zdolności poznawcze, są znacznie nie naruszone. Zespół ten jest często określana jako ciężka niezręczność. Asperger syndrome-one of the five general development disorders characterized by severe difficulties in social relations and limited, stereotypical, repetitive repertoire of interests and activity. Autism is different, above all, that speech and cognitive abilities are not affected. The team is often referred to as severe awkwardness. Asperger syndrome belongs to the category of comprehensive development disorders. In the classification system-the DSM-5 – Asperger's syndrome does not occur, while there is a autism spectrum disorder. Symptoms of Asperger syndrome include: verbal and nonverbal communication disorders, self-centeredness, impaired social skills, stereotype behavior, narrow interests, coordination problems. Manifestation of symptoms changes during life. Place the correct diagnosis is difficult, especially in adults. Most children with Asperger's syndrome do not require drug therapy. Sometimes the use of drugs may be recommended due to the associated symptoms-depression, anxiety, severe rituals, obsessions. Medication may also be used in the case of severe disorders of attention span, impulsiveness and hypermotility, aggression. How the dosage usually does not require their administration in the school.